2013
DOI: 10.1016/j.patcog.2012.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Automated delineation of lung tumors from CT images using a single click ensemble segmentation approach

Abstract: A single click ensemble segmentation (SCES) approach based on an existing “Click&Grow” algorithm is presented. The SCES approach requires only one operator selected seed point as compared with multiple operator inputs, which are typically needed. This facilitates processing large numbers of cases. Evaluation on a set of 129 CT lung tumor images using a similarity index (SI) was done. The average SI is above 93% using 20 different start seeds, showing stability. The average SI for 2 different readers was 79.53%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
85
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 128 publications
(85 citation statements)
references
References 39 publications
(32 reference statements)
0
85
0
Order By: Relevance
“…While all 41 CT volumes have been used in prior studies [21][22][23][25][26][27], they have never been used as a set for the comparison of segmentation algorithms, as we present here, and there therefore is no scientific overlap between the work described here and prior publications.…”
Section: Datasetsmentioning
confidence: 99%
See 2 more Smart Citations
“…While all 41 CT volumes have been used in prior studies [21][22][23][25][26][27], they have never been used as a set for the comparison of segmentation algorithms, as we present here, and there therefore is no scientific overlap between the work described here and prior publications.…”
Section: Datasetsmentioning
confidence: 99%
“…A single click ensemble segmentation (SCES) algorithm using a proprietary platform [27] was used for lung nodule segmentation as seen in Fig. 1.…”
Section: Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…They evaluated the predictive values of more than 400 textural and shape-and intensity-based features extracted from the computed tomography (CT) images acquired before treatment. Tumor volumes were delineated either by radiation oncologists or using semiautomatic segmentation methods [16,17]. A subset of radiomic features were identified for predicting patient survival and describing intra-tumoral heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…In prior work, it has been found that the reproducibility of features depend on the robust of segmentation algorithms, which should provide an accurate and reproducible results [5]. Furthermore, semi-automated segmentation have a better similarity index (SI) than manual segmentation (the SI of machine-segmented lesions SI >0.93, whereas the SI of manual segmentation SI was 0.73) [6]. In this article, a semi-automated segmentation method based on CV model was used twice (obtained 2 data set: test and retest) to get tumor region for CT images of 35 NSCLC patients (15 adenocarcinoma and 20 epidermoid carcinoma).…”
Section: Introductionmentioning
confidence: 99%